2018
DOI: 10.1093/hmg/ddy418
|View full text |Cite|
|
Sign up to set email alerts
|

Persistent upregulation of the β-tubulin tubb6, linked to muscle regeneration, is a source of microtubule disorganization in dystrophic muscle

Abstract: In healthy adult skeletal muscle fibers microtubules form a three-dimensional grid-like network. In the mdx mouse, a model of Duchenne muscular dystrophy (DMD), microtubules are mostly disordered, without periodicity. These microtubule defects have been linked to the mdx mouse pathology. We now report that increased expression of the beta 6 class V β-tubulin (tubb6) contributes to the microtubule changes of mdx muscles. Wild-type muscle fibers overexpressing green f luorescent protein (GFP)-tubb6 (but not GFP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 65 publications
2
42
0
1
Order By: Relevance
“…Tubb6 knockdown was found to be beneficial for microtubule organization in the DMD mouse model (Randazzo et al, 2019). Moreover, Tubb6 levels were higher in myofibers with central nuclei, suggesting a role in regeneration (Randazzo et al, 2019). Consistently, markers of regeneration are higher in shPab muscles (Olie et al, 2019), and we show that cytoskeleton disorganization in shPAB 2D cell culture is causally linked to reduced myogenesis.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Tubb6 knockdown was found to be beneficial for microtubule organization in the DMD mouse model (Randazzo et al, 2019). Moreover, Tubb6 levels were higher in myofibers with central nuclei, suggesting a role in regeneration (Randazzo et al, 2019). Consistently, markers of regeneration are higher in shPab muscles (Olie et al, 2019), and we show that cytoskeleton disorganization in shPAB 2D cell culture is causally linked to reduced myogenesis.…”
Section: Discussionsupporting
confidence: 69%
“…Disrupted microtubule structures have been observed in muscular dystrophies such as Duchenne muscular dystrophy (DMD) (Khairallah, Shi et al, 2012). In a recent study, disrupted microtubule organization was found to be associated with higher levels of tubulin proteins (Randazzo, Khalique et al, 2019). We also found elevated levels of tubulin proteins in the shPab proteome, including β-tubulin6 (Tubb6) (Olie et al, 2019).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Disrupted microtubule structures have been observed in muscular dystrophies such as Duchenne muscular dystrophy (DMD) 43 . In a recent study, disrupted microtubule organization was found to be associated with higher levels of tubulin proteins 44 . We also found elevated levels of tubulin proteins in the shPab proteome, including β-tubulin6 (Tubb6) 5 .…”
Section: Discussionmentioning
confidence: 93%
“…It has been observed that, instead of well-organized microtubule lattice, DMD skeletal muscles showed largely disarranged microtubules. This was associated with the overexpression of the specific isoform of tubulin (beta 6 class V β-tubulin) pointing to the possible important role of this overexpression in DMD [153]. The study of mitochondrial bioenergetics demonstrated that, in permeabilized skeletal muscle fibers from mdx mice, the maximal rates of mitochondrial respiration were about twice lower than those of controls and similar changes were observed in skeletal muscle biopsies from DMD patients.…”
Section: Cytoskeletal-mitochondria Interactions In Pathologymentioning
confidence: 86%